Neural differentiation in perspective: mitochondria as early programmers - Farahani, Ramin M. (Frontiers in Neuroscience, 2025)
Neural differentiation during development of the nervous system has been extensively studied for decades. These efforts have culminated in the generation of a detailed map of developmental events that appear to be associated with emergence of committed cells in the nervous system. In this review the landscape of neural differentiation is revisited by focusing on abiotic signals that play a role in induction of neural differentiation. Evidence is presented regarding a chimeric landscape whereby abiotic signals generated by mitochondria orchestrate early events during neural differentiation. This early stage, characterised by mitochondrial hyperactivity, in turn triggers a late stage of differentiation by reprogramming the activity of biotic signals.